PERANCANGAN SISTEM INFORMASI MONITORING PERKEMBANGAN SKRIPSI DAN EARLY WARNING BERBASIS SMS GATEWAY PADA PRODI INFORMATIKA FAK. TEKNIK UNTAN - Putra, Randhie Akbar Mula (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
The process of counseling student thesis hasbeen done often assessed sluggish, causing studentsand faculty not to a strict schedule so that constructionconsultation thesis thesis students become protractedand even abandoned. Therefore, for the sake of timeefficiency and performance of lecturers and students, we need a system that can monitor and report onprogress of thesis students to students, faculty andparents of students. The purpose of this study was toproduce a system of monitoring the development ofinformation and early warning of thesis-based SMSgateway that can assist in the completion of the thesiswriting process to run smoothly and optimally.Information systems are built to provide studentprogress reports skirpsi, recapitulation studentsmentored by faculty, students report past its guidanceand early warning in the form of SMS messagesautomatically sent to the mobile phones of students,faculty and parents of students if there are studentswho do not do counseling thesis within the allottedtime.The results of the analysis and testing of black-boxmethods shows that an information system monitoringand early warning of thesis-based SMS gateway canrun well and help facilitate communication betweenfaculty and students in the process of ongoingcounseling thesis.